Management instructions for elderly patients with hypertension - Yoshiyuki Ikeda; Takeshi Sasaki; So Kuwahata; Masakazu Imamura; Kanyo Tanoue; Shinichirou Komaki; Mamoru Hashiguchi; Atsushi Kuroda; Yuichi Akasaki; Mitsuru Ohishi (Clinical and Experimental Hypertension, 2020)
Aim: To compare the understanding of hypertension and antihypertensive treatment in Japanese patients (aged <75 years vs. ≥75 years) with blood pressure (BP) targets as per the 2014 Japanese guidelines. Methods: A 10-question survey was administered before and after treatment. Results: Majority of patients aged ≥75 years did not achieve their BP targets (75%); >50% of these patients had little knowledge of hypertension and poor understanding of their physician’s explanation of it. Conclusions: Elderly patients with hypertension (aged ≥75 years) require daily BP monitoring and detailed and repeated explanation of hypertension and BP targets.